NUMERICAL MODELLING AND EXPERIMENTAL INVESTIGATION OF MASS TRANSFER EFFECT DURING CO2 ENHANCED OIL RECOVERY AND STORAGE IN SANDSTONE RESERVOIRS - SAYED REZK, MOHAMED GAMAL (2020)
With the urgent need to reduce greenhouse gas emission in the atmosphere and to improve oil recovery from oil fields, carbon dioxide (CO2) injection is considered one of the most promising enhanced oil recovery (EOR) methods.